Namibia's children living conditions and life forces in a society in crisis - Fink, Michaela 1973-; Gronemeyer, Reimer 1939- (Global studies, 2021)
Many children in Namibia find themselves facing a social crisis. They have been abandoned or abused, are malnourished, homeless, or live in shacks that barely provide any protection. However, amidst these disastrous living conditions, children have developed remarkable survival skills, and come up with equally clever and disillusioned analyses of their situation.For three years, Michaela Fink and Reimer Gronemeyer conducted interviews in Namibia with women who take care of vulnerable children. The book gives these children a voice in interviews and essays